Survey Potensi Pembangkit Listrik Tenaga Mikro Hidro di Kuta Malaka Kabupaten Aceh Besar Propinsi Nanggroe Aceh Darussalam - Ridwan Arief Subekti (National Research and Innovation Agency, 2010)
Generator set is one of the devices able to produces electrics. Generator set used when electrics supply of PLN insufficient or even there no. This matter experienced in Kuta Malaka, Aceh Besar, Nanggroe Aceh Darussalam there will be developed a tour area. Because electrical supply from PLN not yet, power electric to support the area used generator set. Future, that tour area apply hydro power station for electrical energy requirement. From that background, the purpose of water potential survey was conducted to get beginning data and information of water power potential as reference to develop PLTMH. The potential survey cover determination of location and head measurement use global positioning system Garmin GPSMAP 76CSx. The other using altimeter, head also was measure manually used the meter by spirit level and string method. The river rate of flow measurement within measuring to speed of rivers flow use propeller devices or current meters brand Flowatch. From data of PLTMH potential survey in Kuta Malaka area known that there are three potential locations able to be developed as PLTMH with effective head 5 until 16 meter and output power 3.7 until 9.1 kW.